EVALUATION OF NURSES’ KNOWLEDGE AND ATTITUDE ON POSTOPERATIVE PAIN MANAGEMENT IN ASTANA HOSPITALS: IMPLICATIONS FOR CONTINUING EDUCATION - Potapova, Anna-Mariya (Nazarbayev University School of Medicine, 2025)
Despite advancements in health care, pain persisting from surgery remains a worldwide problem for many patients left to cope with unrelieved pain. It is well known that pain management plays one of the most appropriate roles in patient rehabilitation, therefore, effective pain control has the potential to improve postoperative outcomes by decreasing pain, improving comfort and reducing complications, promoting recovery and enhancing satisfaction with care (Umuhoza et al., 2019). Although the importance of effective postsurgical pain management is currently recognized, there are still barriers for achieving it. Attitudes of health care providers toward pain, their knowledge and awareness often come in the way of receiving proper levels of interventions for pain relief. The importance of the nurses’ role in pain management during the postoperative period is emphasized, since they are often the first caregivers to assess pain, administer interventions for pain relief and observe responses from patients. The knowledge and attitudes of nurses towards pain management are vital to effective postoperative care in Kazakhstan but little is known about both. This study aims to assess the gaps in training by evaluating the current levels of knowledge and attitudes of nurses in Kazakhstan while also identifying opportunities for continuing education. Making efforts to fill these gaps can improve pain management and promote more rapid recovery with increased satisfaction level by the patient and family, highlighting the pivotal role of the nurse in optimizing postoperative care.
Keywords: postoperative pain management; nurses' role in pain management; pain assessment; knowledge and attitudes towards pain; nursing care; nursing education; type of access: embargo